Serum Interleukin‐8, Osteopontin, and Monocyte Chemoattractant Protein 1 Are Associated With Hepatic Fibrosis in Patients With Nonalcoholic Fatty Liver Disease. Issue 11 (21st September 2018) - Glass, Oliver; Henao, Ricardo; Patel, Keyur; Guy, Cynthia D.; Gruss, Hans J.; Syn, Wing‐Kin; Moylan, Cynthia A.; Streilein, Robert; Hall, Russell; Mae Diehl, Anna; Abdelmalek, Manal F.
Abstract : The severity of hepatic fibrosis is the primary predictor of liver‐related morbidity and mortality in patients with nonalcoholic fatty liver disease (NAFLD). Unfortunately, noninvasive serum biomarkers for NAFLD‐associated fibrosis are limited. We analyzed baseline serum samples for 24 cytokines of 97 patients with biopsy‐proven NAFLD. These patients were prospectively enrolled in a clinical study (ClinicalTrials.gov NCT00794716) to identify cytokines associated with liver fibrosis in patients with nonalcoholic steatohepatitis. Patients were stratified according to severity of hepatic fibrosis (mild, stage 0‐1, n = 37; moderate, stage 2, n = 40; and advanced, stage 3‐4, n = 20) while controlling for age, race, sex, body mass index, and diabetes mellitus. Interleukin‐8 (IL‐8), osteopontin (OPN), and monocyte chemoattractant protein 1 (MCP1) were associated with liver fibrosis ( P < 0.001, P = 0.005, P = 0.016, respectively). After controlling for steatosis, lobular inflammation, hepatocyte ballooning, age, sex, body mass index, diabetes mellitus, hypertension, and metabolic syndrome status, IL‐8 remained strongly associated with fibrosis ( P = 0.001). Furthermore, IL‐8 was also a strong predictor of increased fibrotic liver injury compared to established markers of hepatic fibrosis. Hepatic gene expression from 72 patients with NAFLD (n = 40 mild fibrosis; n = 32 advanced fibrosis) from the Duke University Health System NAFLD Clinical Database and Biorepository revealed IL‐8, MCP1, and OPN gene expression to be increased and differentially expressed in patients with advanced hepatic fibrosis. Thus, serum IL‐8, MCP1, and OPN may reflect up‐regulated gene expression during liver fibrosis in NAFLD. Conclusion: Serum IL‐8, MCP1, and OPN may serve as a test for advanced hepatic fibrosis in NAFLD and thus reveal novel targets for antifibrotic therapies. The increased serum IL‐8, MCP1, and OPN that correspond with associated hepatic gene expression lend strength to such analytes as ideal surrogate serum biomarkers for severity of hepatic fibrosis. Abstract : Serum Interleukin‐8, Osteopontin, and Monocyte Chemoattractant Protein‐1 are independently associated with hepatic fibrosis in patients with histologically confirmed NAFLD. Moreover, serum Interleukin‐8 levels may mirror hepatic gene expression, serving as an non‐invasive biomarker of hepatic fibrosis. In comparison with other established non‐invasive markers of liver fibrosis, Interleukin‐8 remains a strong predictive biomarker of fibrosis.